A Novel Flow Cytometry-Based Assay for the Identification of HCN4 CNBD Ligands - Magdalena N. Wojciechowski; Sebastian Schreiber; Joachim Jose (MDPI AG, 2023)
Hyperpolarization-activated and cyclic nucleotide-gated (HCN) channels are promising therapeutic targets because of their association with the genesis of several diseases. The identification of selective compounds that alter cAMP-induced ion channel modulation by binding to the cyclic nucleotide-binding domain (CNBD) will facilitate HCN channel-specific drug development. In this study, a fast and protein purification-free ligand-binding approach with a surface-displayed HCN4 C-Linker-CNBD on E. coli is presented. 8-Fluo-cAMP ligand binding was monitored by single-cell analysis via flow cytometry, and a Kd-value of 173 ± 46 nM was determined. The Kd value was confirmed by ligand depletion analysis and equilibrium state measurements. Applying increasing concentrations of cAMP led to a concentration-dependent decrease in fluorescence intensity, indicating a displacement of 8-Fluo-cAMP. A Ki-value of 8.5 ± 2 µM was determined. The linear relationship of IC50 values obtained for cAMP as a function of ligand concentration confirmed the competitive binding mode: IC50: 13 ± 2 µM/16 ± 3 µM/23 ± 1 µM/27 ± 1 µM for 50 nM/150 nM/250 nM/500 nM 8-Fluo-cAMP. A similar competitive mode of binding was confirmed for 7-CH-cAMP, and an IC50 value of 230 ± 41 nM and a Ki of 159 ± 29 nM were determined. Two established drugs were tested in the assay. Ivabradine, an approved HCN channel pore blocker and gabapentin, is known to bind to HCN4 channels in preference to other isoforms with an unknown mode of action. As expected, ivabradine had no impact on ligand binding. In addition, gabapentin had no influence on 8-Fluo-cAMP's binding to HCN4-CNBD. This is the first indication that gabapentin is not interacting with this part of the HCN4 channel. The ligand-binding assay as described can be used to determine binding constants for ligands such as cAMP and derivatives. It could also be applied for the identification of new ligands binding to the HCN4-CNBD.